FORENSIC LINGUISTICS ANALYSIS OF VIRGINIA WOOLF’S SUICIDE NOTES - Malini, Ni Luh Nyoman Seri; Tan, Venessa (International Journal of Education, 2016)
Virginia Woolf was a British writer. She committed suicide in 1941, leaving suicide notes for her sister and her husband. Her suicide note was made public and was misquoted under the misleading headline in newspapers’ articles. This made people at that time misinterpret her suicide notes. This analysis aims to prove the genuineness of Virginia Woolf’s suicide notes, reveal the intention behind her suicide notes, and investigate the real motive of her suicide with Linguistics Inquiry and Word Count (LIWC) program and semantic forensic analysis in forensic linguistics perspective. In conclusion, Virginia Woolf’s suicide notes are considered genuine and have positive emotional tone. The result of this analysis supports the statement of another psychologist that her suicide was triggered by Bipolar disorder.